Microsatellite data - Harris, Les N.; Moore, Jean-Sébastien; Bajno, Robert; Tallman, Ross F. (Dryad Digital Repository, 2016)
Genepop file (3 digit format) containing all microsatellite data. Population names are listed in Table 1 of the paper.